APLIKASI PERKEMBANGAN TEKNIK IN VITRO DAN ANALISIS FLOW CYTOMETY UNTUK MENINGKATKAN PENYEDIAAN SENYAWA METABOLIT SEKUNDER TANAMAN - Santoso, Agus Muji (Universitas Nusantara PGRI Kediri, 2014)
Today’s, higher population cause the human necessary not only at basic food but also at medical compounds has increased too (quality and quantity). The bad impact of modern therapy cause the society should look for the alternative therapy specifically using medical compounds from tropical plants as well as can be found in their environment. Providing medical compounds by tropical plant by conventional methods were inefficient, such us the limitation of reproduction ability plant (by vegetative or generative), were dependent to host plant (medical plant parasite), most of medical plants belonging to rare plant, and the fluctuation of concentration medical compounds will be crucial problem to fulfill their necessary. Based on previous study showed that the improvement of plant tissue culture technique included of the invention and growth plant substances application were able to solve the providing callus as source of medical compounds. However, the higher rate of variation genetic callus caused the variation of medical compounds profile. Biology molecular technology such us flow cytometric and RAPD have great potential to monitor of callus profile, for examples DNA profile or stage of callus cells. Finally, the providing of medical compounds can be filled not only by quality and quantity.